THE DISTURBANCES OF THE RHYTHM AND CONDUCTIVITY IN MITRAL VALVE PROLAPSED OF I DEGREE AT YOUNG AGED PEOPLE - B. I. Mukhiddinov; T. A. Abdullayev (Евразийский Кардиологический Журнал, 2015)
Aim. Examine the frequency and nature rhythm and conduction disorders of a heart in young people with I degree mitral valve prolapse. Material and methods. Examined 85 men aged 18-38 with I degree mitral valve prolapse without mitral regurgitation. Investigation program included medical examination, registration of ECG room on a 12 - lead «Hellidge», Holter ECG monitoring, echocardiogram. Results. Holter ECG can detect rare forms of rhythm and conduction disorders of a heart, uncommitted during ECG recording in 12 standard leads. In patients with MVP 1 degree high grade ventricular arrhythmias recorded in 12% of cases. AV blockade of I and II degrees are three times more likely to occur when HM ECG compared with the registration of standard 12-lead ECG. Most often it is identified AV blockade of II degrees according to daily ECG monitoring during the night. Conclusion. In the examination of young people of military age involvement into broad practice of Holter ECG is prospective direction.